Konsep Pengelolaan Arsip Elektronik - Titis Pratiwi (Pusat Publikasi Ilmiah UIN Fatmawati Sukarno Bengkulu, 2017)
The purpose of writing this article is to explain the concept of electronic records management. Electronic archives have an important role in the administration system. Electronic archives are archives that are created, communicated, stored, and accessible via electronic devices. The development of information technology requires that archives be processed electronically. In managing electronic archives, it requires special knowledge and skills in archival governance coupled with computer knowledge or information technology. Therefore, there needs to be a good collaboration between archivists as archival professionals with programmers as computer professionals to create a good electronic archival management system. Archives stored in electronic form may be images, sounds, video, text or otherwise that can be processed in computer programs and stored in electronic data storage media and can be accessed by electronic media.